In a novel autoimmune and high-pressure glaucoma model a complex immune response is induced - Reinehr, Sabrina; Wulf, Julien; Theile, Janine; Schulte, Kim K.; Peters, Marcus; Fuchshofer, Rudolf; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Immunology, 2024)
Background: The neurodegenerative processes leading to glaucoma are complex. In addition to elevated intraocular pressure (IOP), an involvement of immunological mechanisms is most likely. In the new multifactorial glaucoma model, a combination of high IOP and ocular antigen immunization leads to an enhanced loss of retinal ganglion cells accompanied by a higher number of microglia/macrophages in the inner retina. Here, we aimed to evaluate the immune response in this new model, especially the complement activation and the number of T-cells, for the first time. Further, the microglia/macrophage response was examined in more detail. Methods: Six-week-old wildtype (WT+ONA) and βB1-connective tissue growth factor (CTGF) mice (CTGF+ONA), a genetic ocular hypertension model, were immunized with 1 mg ONA (optic nerve antigen). A wildtype control (WT) and a CTGF group (CTGF) received NaCl instead. Six weeks after immunization, retinae from all four groups were processed for immunohistology, RT-qPCR, and flow cytometry, while serum was used for microarray analyses. Results: We noticed elevated numbers of C1q+ cells (classical complement pathway) in CTGF and CTGF+ONA retinae as well as an upregulation of C1qa, C1qb, and C1qc mRNA levels in these groups. While the terminal complement part C3 was only increased in CTGF and CTGF+ONA retinae, enhanced numbers of the terminal membrane attack complex were noted in all three glaucoma groups. Flow cytometry and RT-qPCR analyses revealed an enhancement of different microglia/macrophages markers, including CD11b, especially in CTGF and CTGF+ONA retinae. Interestingly, increased retinal mRNA as well as serum levels of the tumor necrosis factor α were found throughout the different glaucoma groups. Lastly, more T-cells could be observed in the ganglion cell layer of the new CTGF+ONA model. Conclusion: These results emphasize an involvement of the complement system, microglia/macrophages, and T-cells in glaucomatous disease. Moreover, in the new multifactorial glaucoma model, increased IOP in combination with autoimmune processes seem to enforce an additional T-cell response, leading to a more persistent pathology. Hence, this new model mimics the pathomechanisms occurring in human glaucoma more accurately and could therefore be a helpful tool to find new therapeutic approaches for patients in the future.